2017
DOI: 10.1016/j.jsbmb.2017.07.031
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer potential of new steroidal thiazolidin-4-one derivatives. Mechanisms of cytotoxic action and effects on angiogenesis in vitro

Abstract: The synthesis and cytotoxic activities determination of new steroidal mono- and bis(thiazolidin-4-ones) 4a-f and 5a-f have been performed. Their anticancer action was also evaluated in comparison to previously synthesized and reported corresponding steroidal thiosemicarbazones. All compounds were obtained as stereoisomeric mixtures with different configuration (E or Z) in the hydrazone moiety at the C-3 position. After several consecutive crystallizations diastereomerically pure major (E)-isomers of mono-thiaz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 32 publications
(60 reference statements)
0
7
0
Order By: Relevance
“…Considering the molecular basis of RCC, the development of targeted agents should also include the inhibitory potential associated with intracellular signal transduction pathways that drive angiogenesis (36). Furthermore, a recent study demonstrated that newly identified steroidal thiazolidin-4-ones exhibited significant anti-angiogenic effects (33). Our future studies may include these novel perspectives.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Considering the molecular basis of RCC, the development of targeted agents should also include the inhibitory potential associated with intracellular signal transduction pathways that drive angiogenesis (36). Furthermore, a recent study demonstrated that newly identified steroidal thiazolidin-4-ones exhibited significant anti-angiogenic effects (33). Our future studies may include these novel perspectives.…”
Section: Discussionmentioning
confidence: 97%
“…In the present study, when the chemical structures of synthesized 1,3-thiazolidin-4-ones were confirmed by spectral data, their anticancer potential was evaluated in in vitro experiments. The thiazolidin-4-one moiety is a biologically proven anticancer pharmacophore and substitution in this scaffold may further enhance its activity (15)(16)30,33). It is known that substituents may be varied but the greatest significance in properties is exerted by the group attached to the carbon atom at the 2-position of the thiazolidinone heterocycle (16).…”
Section: Discussionmentioning
confidence: 99%
“…Živković et al [ 37 ] designed a series of mono- and bis-4-thiazolidinone-containing hybrids with androstene derivatives. For the synthesized hybrids, anticancer activity studies were performed on six cancer lines: HeLa (cervical adenocarcinoma), K562 (chronic myelogenous leukemia), MDA-MB-453 (breast carcinoma), MDA-MB-361 (breast adenocarcinoma), LS174 (colon adenocarcinoma), A549 (lung carcinoma), and MRC-5 (normal lung fibroblast line).…”
Section: Natural Compound Scaffold–4-thiazolidinones Hybridsmentioning
confidence: 99%
“…In recent years, the chemistry of 4‐thiazolidinone derivatives has been the subject of intense research by biologists and organic chemists because such compounds represent substantial scaffolds in drug discovery . According to this approach, thiazolidin‐4‐ones have been reported to own wide spectrum of biological activity such as antimicrobial , antitubercular , antitumoral , anticancer , anti‐inflammatory , antiglioma , anticonvulsant , anti‐HIV‐1 , antioxidant , and analgesic properties .…”
Section: Introductionmentioning
confidence: 99%